2021
DOI: 10.3389/fnut.2021.799035
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing and Measuring Appetite Self-Regulation Phenotypes and Trajectories in Childhood: A Review of Person-Centered Strategies

Abstract: This review uses person-centered research and data analysis strategies to discuss the conceptualization and measurement of appetite self-regulation (ASR) phenotypes and trajectories in childhood (from infancy to about ages 6 or 7 years). Research that is person-centered provides strategies that increase the possibilities for investigating ASR phenotypes. We first examine the utility of examining underlying phenotypes using latent profile/class analysis drawing on cross-sectional data. The use of trajectory ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 120 publications
0
4
0
Order By: Relevance
“…In this approach, instead of treating eating behaviours as single constructs, researchers conceptualize eating behaviours in terms of phenotypes that include patterns or collections of behaviours related to differences in eating behaviours/phenotypes in sub-groups of children. This approach assumes that the person is an integrated totality whose behaviours are interwoven and interacting over time [ 192 , 193 ]. It is a data driven and exploratory approach [ 193 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this approach, instead of treating eating behaviours as single constructs, researchers conceptualize eating behaviours in terms of phenotypes that include patterns or collections of behaviours related to differences in eating behaviours/phenotypes in sub-groups of children. This approach assumes that the person is an integrated totality whose behaviours are interwoven and interacting over time [ 192 , 193 ]. It is a data driven and exploratory approach [ 193 ].…”
Section: Discussionmentioning
confidence: 99%
“…This approach assumes that the person is an integrated totality whose behaviours are interwoven and interacting over time [ 192 , 193 ]. It is a data driven and exploratory approach [ 193 ]. Its contribution at present seems mainly to suggest the presence of different phenotypes that involve a combination or pattern of individual eating behaviours and eating behaviour trajectories.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are different approaches to quantifying the cumulating effects of multiple stressors: 1) adding up the number of stressors; 2) using a composite score to factor in both the number of exposures and the contribution of individual stressors in the overall measure (Slopen and Cuevas, 2021); 3) applying a person-centered approach, e.g., latent profile analysis (LPA), to discover naturally-occurring clusters of individuals with similar patterns of stress exposures and explore the differences across classes (Merians et al, 2019). Studies have shown that person-centered approaches could provide insights into how stressors might be organized and interrelated at an individual level and may help to better conceptualize and measure multiple stressors (Russell et al, 2021).…”
Section: Introductionmentioning
confidence: 99%